Ekspresi Perasaan Cinta Tokoh Utama dalam Drama Love Is Phantom - Akram, Andi Nurnisa Rofifah; Anwar, Fithyani (KIRYOKU, 2025)
This research aims to analyze the love languages portrayed by the main characters in the drama "Love is Phantom" based on Gary Chapman's The Five Love Languages theory. The study employs a qualitative descriptive method with a structural approach to explore the meaning behind the main characters' interactions. Data was collected through observation and note-taking of dialogues, narratives, and scenes in the drama that demonstrate expressions of the five love languages. The findings reveal that all five love languages are present in the drama, with physical touch being the most frequently used. The male protagonist Hase Kei's primary love language is physical touch, while the female protagonist Hirasawa Momoko predominantly expresses acts of service. Despite having different primary love languages, the relationship between the two characters remains harmonious as they also utilize secondary love languages to meet their partner's needs—Kei employs words of affirmation, and Momoko uses physical touch. The research concludes that understanding a partner's love language contributes significantly to relationship harmony.